The Quality of Urban Living - Böhm, Aleksander (Journal of Public Governance, 2021)
Objectives: This paper presets the different factors of living in an urban space, as well as their implications. Research Design & Methods: The mosaic of the different ways of living in a modern city is currently influenced by a new phenomenon (till now only partially recognised), namely the advancement of information technology. The article assumes the form of the overview of the history of the development of modern city. Findings: Comparing and estimating different results of urban innovations can serve as the best practice for urban planning. Implications / Recommendations: Eliminating the disadvantages and retaining the main advantage of a “flat with own garden” – now called smart sprawl – seems to be a permanent and long-lasting tendency. Contribution / Value Added: The paper is a contribution to the list of the contemporary problems such as urban sprawl, Transport-Oriented Development, telecommuting, and the role of the public space.